Preventive Legal Mechanisms in Real Property Transactions: Ensuring Legal Certainty - Merline Eva Lyanthi; Rosalinda Elsina Latumahina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2026)
Land disputes remain a persistent challenge in Indonesia despite the enactment of the Basic Agrarian Law (UUPA) in 1960, which marked a foundational transformation in the national land law system and mandated systematic land registration across the country. The high volume of unresolved disputes, as reflected in the 5,973 land cases recorded by the Ministry of ATR/BPN in 2024, signals a continued weakness in preventive legal protection mechanisms within land transactions, particularly in the residential sector. This study examines the forms of preventive legal protection applicable to residential land sale and purchase transactions, the obstacles to their implementation, and the efforts required to guarantee legal certainty for all parties involved. Employing a normative juridical method with a statute approach and a conceptual approach, this study analyzes primary legal materials including the UUPA, Government Regulation Number 24 of 1997, and the Civil Code, supported by secondary sources comprising academic literature and relevant court decisions. The findings indicate that preventive legal protection operates through several mechanisms, such as land registration, pre-transaction verification, the preparation of authentic deeds by a Land Deed Official (PPAT), compliance with agreement validity requirements, tax obligation fulfillment, legal outreach, and digitalization of land services. Adherence to these mechanisms reduces dispute risk by up to 70%, yet implementation remains hampered by low public legal awareness, land mafia practices, weak oversight, and bureaucratic complexity. This study contributes to agrarian and civil law scholarship by affirming the primacy of a preventive paradigm over reactive dispute resolution in ensuring legal certainty for all stakeholders in residential land transactions.